Ultra-Low-Profile Small-Size LTCC Front-End Module (FEM) for WLAN Applications based on a Novel Diplexer Design Approach - Sakhnenko, Sergiy; Orlenko, Denys; Vorotnikov, Borys; Aleksieiev, O.; Komakha, P.; Heide, Patric; Vossiek, Martin (IEEE 2009 International Microwave Symposium (IMS 2009), 2009)
This paper reports on the design of a very compact dual-band highly-integrated front-end module for size-critical wireless applications supporting IEEE 802.11a/b/g standards. The module consists of two novel high-rejection lumped-element diplexers which are connected to one common antenna via single-pole-double-through (SPDT) switch. The novelty of the realized diplexers consists in a new conjugatematching method which allows to design very compact diplexers without additional matching networks. The LTCC integrated diplexers are placed between two ground planes ensuring high electromagnetic compatibility which allows using them as building blocks of the highly-integrated wireless LAN (WLAN) front-end module. The physical dimensions of the complete module are 3.0x3.0x0.95 mm. Up to date this is a smallest LTCC-based switch-diplexer FEM published so far. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.ultral
Keywords: Diplexers; Filters; Front-end module; LTCC; WLAN